Perceived Coaches’ Attributes and Level of Fitness Skills Performance Among Student-Athletes (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
Good engagement of sports towards education enables the students to balance academic learning and sports skill acquisition. This study sought to find the relevance of perceived coaches’ attributes on the result of evaluation to the performance of student-athletes to produce successful athletes and coaches. It utilized descriptive-correlational research design to determine the significant relationship between attributes of school coaches and sports fitness skill performance of N=162 student-athletes. Instruments used were standardized Coaching Behavior Scale for Sports CBS-S and Standardized Sports Performance Physical Fitness Skill Test. The results disclosed that the sports fitness performance of the student-athletes according to cardiovascular endurance, agility, muscular strength, and flexibility were on highest level; power, reaction-time, and speed were on high level; balance was on average level; muscular endurance and coordination were on low level. It is concluded that the behavior of a coach may determine his competency in designing effective training, hence influence excellent achievement among athletes. Thus, an active engagement of sports towards education enables the students to balance academic learning and sports skill acquisition.